2017
DOI: 10.1007/s10072-017-3001-y
|View full text |Cite
|
Sign up to set email alerts
|

SAND: a Screening for Aphasia in NeuroDegeneration. Development and normative data

Abstract: Language assessment has a critical role in the clinical diagnosis of neurodegenerative diseases, in particular, in the case of Primary Progressive Aphasia (PPA). The current diagnostic criteria (Gorno-Tempini et al., 2011) identify three main variants on the basis of clinical features and patterns of brain atrophy. Widely accepted tools to diagnose, clinically classify, and follow up the heterogeneous language profiles of PPA are still lacking. In this study, we develop a screening battery, composed of nine te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 44 publications
2
50
0
2
Order By: Relevance
“…However, to verify whether the present sample size could make our inter-form parallelism analysis unreliable, we run a power analysis on an unconstrained measurement model (all loadings and error variances free to vary, according to Muthén and Muthén,[40]). The results of this analysis (Supplementary [42][43][44]). We conformed to this practice, also for the sake of consistency among Italian normative data.…”
Section: Discussionmentioning
confidence: 99%
“…However, to verify whether the present sample size could make our inter-form parallelism analysis unreliable, we run a power analysis on an unconstrained measurement model (all loadings and error variances free to vary, according to Muthén and Muthén,[40]). The results of this analysis (Supplementary [42][43][44]). We conformed to this practice, also for the sake of consistency among Italian normative data.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a systematic review identified the few neuropsychological tests available for the assessment of speech and language disorders in PPA and discussed their limitations [7]. This is the main reason that led to the development of the SAND battery [8]. In this study, we explored its clinical validity and psychometric characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…All participants were given the SAND battery, whose normative values have already been published [8]. The entire battery takes < 20 min to administer and yields scores for each of the nine subtests.…”
Section: Sand Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is likely a high heterogeneity in tests and cutoffs used in the diagnosis of PPA across different clinical and research sites. There is a need for a use of sensitive and specific tests, and some authors have recently published assessment batteries specifically designed for the assessment of PPAs ( 157 , 158 ). Most importantly, apparently similar symptoms might be due to distinct underlying causes between PPA variants, and this should be considered in tests selection and interpretation.…”
Section: Variants Of Primary Progressive Aphasia (Ppa)mentioning
confidence: 99%